Association between ADAMTS7 TagSNPs and the risk of myocardial infarction. Issue 1127 (10th July 2019) - Liang, Li-li; Zhou, Yu-lan; Cheng, Jie; Xiao, Yu-tong; Tang, Zi-bin; Liu, Sun-min; Lian, Jia-chun; Wang, Xin-xin; Liu, Xinguang; Xiong, Xing-dong
Abstract: Purpose of the study: Genome-wide association studies have revealed an association of ADAMTS7 polymorphisms with the risk of cardiovascular diseases. Nonetheless, the role of ADAMTS7 polymorphisms on myocardial infarction (MI) risk remains poorly understood. Here, we aim to evaluate the effect of ADAMTS7 tag single nucleotide polymorphisms (SNPs) on individual susceptibility to MI. Study design: Genotyping of the four tagSNPs (rs1994016, rs3825807, rs4380028 and rs7173743) was performed in 232 MI cases and 661 control subjects using PCR-ligase detection reaction (LDR) method. The association of these four tagSNPs with MI risk was performed with SPSS software. Results: Multivariate logistic regression analysis showed that ADAMTS7 tagSNP rs3825807 exhibited a significant effect on MI risk. Compared with the TT homozygotes, the CT genotype (OR1.93, 95% CI1.30to 2.85, Pc =0.004) and the combined CC/CT genotypes (OR1.70, 95% CI1.16 to 2.50, Pc =0.028) were statistically significantly associated with the increased risk for MI. Further stratified analysis revealed a more significant association with MI risk among older subjects, hypertensives, non-diabetics and patients with hyperlipidaemia. Consistently, the haplotype rs1994016T–rs3825807C containing rs3825807 C allele exhibited increased MI risk (OR1.52, 95% CI1.10 to 2.10, p=0.010). However, we did not detect any association of the other three tagSNPs with MI risk. Conclusions: Our finding suggest that ADAMTS7 tagSNP rs3825807 contributes to MI susceptibility in the Chinese Han population. Further studies are necessary to conﬁrm the general validity of our ﬁndings and to clarify the underlying mechanism for this association.